Applicability of Malaysian Standards (MS 966) in benefiting health and safety of children in Malaysia - Cheah, Kah Ling; Raja Ahmad Effendi, Raja Ahmad Azmeer; Dolah, Mohd Shahrizal; Ramli, Saiful Hasley; Bolong, Jusang (Universiti Putra Malaysia Press, 2019)
Child injuries caused by unsafe climbing equipments has become a public concern. The Malaysian Standards for playground equipment (MS 966: 2001 and MS 966: 2017) was developed and reviewed periodically by the authority of the Consumer Products, Personal Safety and Services Industry Standards Committee, Department of Standards Malaysia (DSM) and SIRIM Berhad, as a means of protecting and benefiting the health and safety of children. This paper aims to examine and critique the applicability of Malaysian Standards on standardizing design specification and safety performance of climbing equipments. The review process focuses on information gaps within the Malaysian Standards in terms of feasibility, where discussions on analytical issues in Malaysian Standards of climbing equipment was presented and recommendations on improvement were proposed. The result showed the standards focused mostly on swings and slides, whilst three analytical issues found that important design and safety standards in climbing equipments were unclear; which included free fall height, maximum height and designated age group. These three analytical issues have to be revised in order to achieve sustainable design in climbing equipment. Results from this paper could assist in revising the current standards incorporated with advanced urban recreation safety for injury control.